Corporate Social Responsibility, Brand Preference, Satisfaction and Loyalty of Thai Consumer on Thai Beer in Bangkok Metropolitan Area - Yansomboon, Supinya; Gulid, Nak (Journal of Ecohumanism, 2025)
This study investigates the influence of corporate social responsibility (CSR) across two dimensions—stakeholder-focused and society-focused—on brand preference, satisfaction, and customer loyalty, including purchase intention and positive word-of-mouth, in the Thai beer industry. This controversial and socially sensitive sector requires careful CSR practices to address public concerns and enhance corporate reputation. Mixed-mode surveys (online and face-to-face interviews) were conducted with 400 Thai beer consumers in Bangkok, and partial least squares structural equation modeling (PLS-SEM) was employed to analyze the data and test the hypotheses. The findings reveal that both stakeholder- and society-focused CSR positively and directly impact brand preference and satisfaction, with stakeholder-focused CSR demonstrating a stronger influence. Satisfaction exerts a greater positive effect on purchase intention, while brand preference shows a stronger impact on positive word-of-mouth. Satisfaction also partially mediates the CSR-loyalty relationship for both dimensions of CSR, while brand preference partially mediates the stakeholder-focused CSR-loyalty pathway. Furthermore, brand differences significantly moderate the effects of CSR on brand preference and satisfaction, underscoring the importance of tailored CSR strategies for different market segments. To enhance customer loyalty and strengthen brand reputation in the Thai beer industry, firms should prioritize stakeholder-focused CSR initiatives that directly benefit stakeholders, such as community programs and employee welfare schemes, as these have a stronger influence on brand preference and satisfaction. Society-focused CSR, such as philanthropic activities and environmental conservation projects, should be leveraged to address broader societal concerns, complementing stakeholder-focused efforts. Effective CSR communication is critical, and firms should clearly communicate CSR initiatives through social media, advertising, and on-pack messaging to build trust and brand preference. Recognizing the moderating role of brand differences, firms are advised to segment CSR strategies by brand, tailoring activities to reflect unique values and positioning. Monitoring and evaluating the impact of CSR initiatives using metrics such as customer satisfaction, brand preference, and loyalty can help refine strategies and maximize their effectiveness. This study provides valuable insights for practitioners and policymakers in managing CSR initiatives within controversial industries. From a managerial perspective, integrating stakeholder-focused and society-focused CSR can foster both attitudinal and behavioral loyalty, enhancing overall brand equity. Policymakers can leverage these findings to encourage responsible corporate behavior in industries that pose potential societal risks, such as alcohol and tobacco. Future research can explore long-term CSR impacts and extend these findings to other industries and cultural contexts to deepen understanding.